(untitled) (Oxford, 1980)
Contents: Part I. Primary production; Part II. Prime movers; Part III. The rise of the electrical industry; Part IV. The chemical industry; Part V. Transport; Part VI. Civil engineering; Part VII. Manufacture; Part VIII. The threshold of the twentieth century
Keywords: Technology,Công nghệ; History,Lịch sử